2016
DOI: 10.1080/15622975.2016.1199893
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume in first-episode schizophrenia and longitudinal course of the illness

Abstract: We replicated the effect of psychosis duration on hippocampal volume already at the time first-episode, which supports the concept of toxicity of psychosis. The indices of a later unfavourable course of schizophrenia had no correlation with baseline brain morphology, suggesting that there is no baseline morphological abnormality of the hippocampus that predisposes the patient to frequent psychotic outbursts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Hýža et al, in a 4‐year longitudinal study found enlarged left CA1 volume in 58 individuals with first‐episode schizophrenia (with a mean duration of untreated psychosis of 7.23 months; 38 with follow‐up clinical data) when compared to 58 healthy controls. They also found a trend‐level negative correlation between duration of untreated psychosis and CA2/3 volume and a positive correlation between right CA1 volume and positive symptom severity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hýža et al, in a 4‐year longitudinal study found enlarged left CA1 volume in 58 individuals with first‐episode schizophrenia (with a mean duration of untreated psychosis of 7.23 months; 38 with follow‐up clinical data) when compared to 58 healthy controls. They also found a trend‐level negative correlation between duration of untreated psychosis and CA2/3 volume and a positive correlation between right CA1 volume and positive symptom severity.…”
Section: Resultsmentioning
confidence: 99%
“…Most schizophrenia imaging studies using FreeSurfer to estimate hippocampal subregion volumes published to date have employed the first method and atlas . Three FreeSurfer studies have used the second method with the updated hippocampal subregion segmentation atlas run on top of the FreeSurfer 5.3 whole hippocampal segmentation …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, it has been well documented that the largest magnitude of subcortical brain volume abnormalities in schizophrenia is in the hippocampus, which can be seen in both the early and chronic stages of this disorder 39,40. Hippocampus is hypothesized to underlie the neuropsychological deficits and symptoms observed in schizophrenia 41,42. Thereby, the role of CFH in schizophrenia could not be excluded, even though we did not detect any association of CFH with schizophrenia at molecular level.…”
Section: Discussionmentioning
confidence: 99%